Predicting Effects of Clinicopathological Variables on Her2 Gene Amplification by Chromogenic in situ Hybridization (CISH) in IHC Her2 (2+) Breast Cancer Patients; A Study from Iran - Hashemi Bahremani, Mohammad (Iran J Pathol, 2020)
BACKGROUND & OBJECTIVE: The her2 amplification plays an important role in breast cancer management. Therefore, there is a need for using supplementary molecular methods in IHC equivocal cases. Present study has been conducted to determine the effects of clinicopathological variables on her2 gene amplification by chromogenic in situ hybridization (CISH) in IHC Her2 (2+) breast cancer individuals. METHODS: A cross-sectional study was conducted in Zaferanyeh Laboratory collaborated with Shahid Beheshti University of Medical Sciences (Tehran-Iran; 2015-2018). All pathological data related invasive breast cancer patients with equivocal IHC results were included. CISH method was performed as a supplementary technique. The associations between histopathologic variables, status of Ki-67 index, progesterone and estrogen receptors (PR & ER) with her2 amplification by CISH were investigated and analyzed. The level of significance was considered as P-value < 0.05. RESULTS: Totally, 239 patients with mean age of 53.2 years were studied. CISH identified her2 gene amplification in 51 subjects (21.3%). The type of tumor (invasive ductal carcinoma), the tumor grade, and the value of Ki-67 index were directly correlated with her2 amplification. Significant negative associations were also observed between CISH results and ER and PR expression. CONCLUSION: As her2 gene amplification was identified in 21.3% of invasive breast cancer patients with equivocal IHC results, it is supposed that applying CISH method may consider as a potentially valuable supplementary method. Results have also shown that higher grades of tumor, invasive ductal carcinoma, absences of hormone receptors and high Ki-67 index significantly correlated with the her2 amplification.